2004
DOI: 10.1007/s00117-004-1125-6
|View full text |Cite
|
Sign up to set email alerts
|

PET-CT-Bildgebung bei Kopf-Hals-Tumoren

Abstract: Fused PET/CT imaging with [F18]-FDG and native CT-scanning enables accurate diagnosis in 93% of lesions and 90% of patients with head and neck oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Reviewing titles and abstracts from Embase revealed 17 articles potentially eligible for inclusion, of which 15 were all already identified by the PubMed/MEDLINE search. Thus, 19 studies [1230] remained for possible inclusion and were retrieved in full text version. Screening of the references of these 19 articles did not bring up new articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing titles and abstracts from Embase revealed 17 articles potentially eligible for inclusion, of which 15 were all already identified by the PubMed/MEDLINE search. Thus, 19 studies [1230] remained for possible inclusion and were retrieved in full text version. Screening of the references of these 19 articles did not bring up new articles.…”
Section: Resultsmentioning
confidence: 99%
“…Screening of the references of these 19 articles did not bring up new articles. After reviewing the full article, two articles [17, 19] were excluded because a part of the study population underwent FDG-PET alone and was not separately analyzed from patients undergoing FDG-PET/CT, two articles [25, 30] were excluded because sensitivity and specificity for primary tumor detection could not be calculated, one article [28] was excluded because it did not separately analyze patients with CUP, one article [21] was excluded because fewer than ten patients with CUP were included, one article [23] was excluded because it was an editorial, and one article [24] was excluded because the same data were used in a later study. Eventually, 11 studies [1216, 18, 20, 22, 26, 27, 29], comprising a total sample size of 433 patients with CUP, met all inclusion and exclusion criteria, and they were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Current National Comprehensive Cancer Network (NCCN) guidelines do not recommend the use of routine follow-up imaging unless clinically indicated and no evidence to demonstrate a benefit of surveillance imaging after 6 months [11]. However, multiple case reports have reported that the use of PET/CT may lead to improved accuracy and earlier detection of cardiac metastases in patients with head and neck cancer [4, 1215]. Some studies have suggested that routine ECG may have a diagnostic value, but findings are often nonspecific, and further confirmation with imaging would be required [1517].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas PET did not have the status of an essential diagnostic requirement in the “guidelines for tumors of the upper aerodigestive tract 2003” [45], to date there has been a paradigm shift. In the meantime, several studies admit the importance of 18F-FDG PET-CT for nodal staging of head and neck squamous cell carcinoma and the cervical CUP syndrome [37], [38], [39], [46], [47], [48]. 18F-FDG PET-CT can provide evidence of a second tumor during staging, considering the fact that in patients with HNSCC there is a 10 to 30-fold higher risk than in the general population for the development of secondary tumors outside the head and neck region.…”
Section: Positron Emission Tomography-computed Tomographymentioning
confidence: 99%